Neueste Karte der Erde : mit Rücksicht auf das Bedürfniss des Handelstandes sowie für den Unterricht an Lehr-Anstalten. - Baur, C. F. (Carl Friedrich) (Julius Maier)
Map shows explored and unknown [Arctic and Antarctic] regions of the world. Routes traveled by a variety of explorers and a weather chart are also shown. Relief shown by hachures. Scale not given.